Pengaruh TATO, FATO, DAR, dan DER Terhadap ROA pada Indeks IDX30 yang Terdaftar di Bursa Efek Indonesia - Rian Sofiani; Dedi Hariyanto; Heni Safitri (Universitas Muhammadiyah Pontianak, 2018)
The company receives additional funds to develop its business by offering and selling part of its shares to the public. The funds obtained are usually used for expansion purposes as well as for debt repayments which are expected to improve the company's financial stability in addition to strengthening the company's working capital structure. The purpose of this study was to determine the effect of Total Assets Turnover (TATO), Fixed Assets Turnover (FATO), Debt to Assets Ratio (DAR), and Debt to Equity Ratio (DER) on Return on Assets (ROA) on the IDX 30 index listed on the Indonesia Stock Exchange. The sampling technique used in this study is the Non Probability method which is by saturating sampling. Based on predetermined sample criteria, a total of 30 companies were obtained. The analysis technique used is normality test, multicollinearity test, autocorrelation test, linearity test, heteroscedasticity test, multiple linear regression analysis, test coefficient of determination (r2), F test (simultaneously), and t test (partially). The results of the normality test showed that all data used as samples were normally distributed with asymp sig. (2-tailed) of 0.539 greater than 0.05. For the results of the determination test shows ROA is influenced by TATO, FATO, DAR, and DER by 81.6%, while the rest is influenced by other factors not examined by 18.4%. For simultaneous testing results using F test shows that the four independent variables, namely TATO, FATO, DAR, and DER together have a significant effect on the dependent variable (stock return) as evidenced by the calculated F value of 27.665 which is greater than F table of 2.92. Whereas for partial testing using the t test shows that the variables FATO, DAR, and DER have no significant effect on ROA while the TATO variable has a significant effect on ROA.